Critical factors in Islamic marketing mix and their relationship with customer satisfaction / Johari Abdullah - Abdullah, Johari (2013)
Recent emergence of the Muslim consumer market has created vast opportunity for new and innovative marketing approaches within an Islamic framework. Thus, Islamic marketing (IM) has attracted considerable attention among scholars and practitioners of business. Nevertheless, this area still remains under-researched with limited empirical data, particularly on marketing mix decisions or the four Ps (product, price, promotion and place) in line with Islamic principles. Therefore, this study attempts to identify critical factors in conducting Islamic marketing mix activities and their relative importance. Using a combination of qualitative and quantitative research methods, this study proposes a set of 23-item instruments that measures the Islamic marketing mix which has been empirically tested for its unidimensionality, reliability and validity through factorial analyses. Findings suggest that Muslim customers consider five critical factors that must be emphasized by businesses in conducting their marketing mix. In their order of importance using multiple regression analysis, the factors are ‘Conformity’, ‘Characteristic’, ‘Confidence’, ‘Conscience’ and ‘Customer Centric’. Hence, it is proposed that businesses adopt the 5Cs framework in engaging with Muslim customers through their marketing mix activities by consistently conforming to Syariah rules and regulations, exhibiting distinctive characteristics, being committed in instilling confidence, embedding morality and conscience and lastly embracing a customer oriented approach.